Contribution of Model 24 to Accident Analysis - Bousfot, Widad; Saadi, Saadia; Djebabra, Mébarek (11th Annual International Conference on Industrial Engineering and Operations Management , March 7-11, 2021)
Workplace accidents (WAs) are and will remain a major concern for organizations’ managers. Their control requires putting in place a prevention strategy framed by several factors (human / social, economic, regulatory ...). The successful implementation of this strategy is conditioned on the ground, by the junction of three essential stages, namely: the analysis, evaluation and control of WAs. These three stages are interdependent where a successful control of an action plan is conditioned by a thorough assessment of an accident risk criticality. The latter depends on a good analysis of the accident. Indeed, a good analysis of WAs largely conditions their prevention strategy and that is why the analysis of WAs occupies a prominent place in such strategies. WAs analysis is conducted using appropriate models referred to as "WAs analysis models". Among those cited in the literature, we quote the model 24 that is a contemporary and more systematic model compared to other models. In this context that this article fits in, which aims to highlight its multiple contributions for the analysis of WAs.